Coconut endosperm fiber effects on blood serum lipids of male domestic rabbits (0ryctolagus Cuniculus lL. 1758) (Asia Life Sciences : the Asian International Journal of Life Sciences, 2009)
The effects of coconut flour on blood lipid parameters in male domestic rabbits (Oryctolagus cuniculus L., 1758) were examined. Four to seven week-old rabbits (n = 28) were fed with different diets for 6 weeks. Seven animals were randomly assigned to each treatment group: Treatment 1 = 2, 600 kcal/kg of feed without coconut flour (A); treatment 2 = 2; 600 kcal/kg of feed with coconut flour (B); treatment 3 = 2,900 kcal/kg of feed without coconut flour (C) and treatment 4 = 2,900 kcal/kg of feed with coconut flour (D). At the start of the study, pretreatment blood serum lipid,(total cholesterol, HDL and, LDL cholesterol and triacylglycerol) concentrations of the rabbits in the four treatment groups, were not significantly different. By the end of week 6, fasting serum triacyl glycerol concentrations significantly decreased (P<0.01) in diets B and D. The fasting serum total cholesterol, low density lipoprotein cholesterol and high density lipoprotein cholesterol concentrations were not significantly different after subjecting the animals to the four diets. This finding provides a basis for studies in humans where any similar effects may have potential benefits in protecting against chronic diseases such as diabetes mellitus and heart disease.